PERANCANGAN VIDEO GAME ”BITTERSWEET RUN” SEBAGAI PENGINGAT BAGI REMAJA KOTA SEMARANG MENGENAI BAHAYA KONSUMSI GULA BERLEBIH - Samuel Paulus Fonda; Dimas Irawan Ihya Ulumuddin (CITRAKARA, 2025)
Sugar is an essential component for the human body, serving as a primary source of energy. However, excessive consumption can lead to adverse health effects. The research adopts a qualitative approach, supported by a literature review and questionnaire data collected from adolescent respondents aged 12 to 20 years in Semarang City. The data obtained will be analyzed using the framing method by Robert N. Entman and needs analysis by Roger S. Pressman. The results of the study indicate that the frequency of consumption of sweet foods and drinks among teenagers in Semarang City is still quite frequent, and a lack of understanding of the dangers of excessive sugar consumption. The game design will be developed using the Multimedia Development Life Cycle (MDLC) method, as introduced by Luther. The video game that was designed is expected to provide benefits, especially by reminding teenagers in Semarang City about the dangers of excessive sugar consumption.